In vivo antioxidant activities of Curcuma longa and Curcuma xanthorrhiza: A review - Lukitaningsih, Endang; Rohman, Abdul; Rafi, Mohamad; Ahmad Fadzillah, Nurrulhidayah; Windarsih, Anjar (Rynnye Lyan Resources, 2020)
Free radicals, reactive nitrogen species (RNS) and reactive oxygen species (ROS) have been known to contribute several degenerative diseases such as cardiovascular diseases, cancers, rheumatoid arthritis, neurodegenerative, and diabetes mellitus. In order to overcome the negative effects of these radicals, some scientist explores natural antioxidants from plants. Curcuma longa (Turmeric) and Curcuma xanthorrhiza (Javanese Turmeric) have been known as herbs and spices with antioxidant activities due to curcuminoid contained. Antioxidant can be defined as any substances or samples capable of inhibiting free radical reactions in the oxidation reaction. Several chemical and biological methods either in vitro or in vivo have been proposed, evaluated, and used for antioxidant evaluation of studied samples. Antioxidant activities in vivo can be measured by determining antioxidant enzymes which include catalase, glutathione reductase, superoxide dismutase, glutathione peroxidase, and glutathione S-transferase. The antioxidant enzymes increased while the lipid peroxidation decreased for both Curcuma species when research using animal models. This present review highlights the potential use of C. longa and C. xanthorrhiza as natural antioxidants in vivo. Based on in vivo studies, Curcuma species are potential sources of natural antioxidants, which can be used as food supplements. © 2019 The Authors. Published by Rynnye Lyan Resources.